The Students’ Perception toward Their English Achievement in International Class Program - Ferawaty Syam; Herman Resyadi (TLEMC (Teaching and Learning English in Multicultural Contexts), 2021)
This study highlights the students’ perception of their English achievement through bilingual programs. The aims of this study were (1) explore the students’ perception of their English achievement on ICP (International Class Program) as a bilingual program, and (2) distinguish the students’ English achievement between bilingual (ICP) and monolingual (regular class) program. This study was navigated by a descriptive qualitative method. To collect the data, this study applied interview and document study. The data were taken purposively from 16 of mathematics students on ICP and regular class as the sample of the study. It was analyzed by data recording, selecting, transcribing, coding, interpreting, and reporting. Data recording was transformed into transcript. The transcription was coded to obtain the extract to be interpreted to find out the main sense of students’ perception on their English achievement. The result of this study exposed that ICP influenced English understanding of mathematics students. Students’ English achievement on ICP is also improved which is proved by their English subject score which is higher than the regular class. It was concluded that the English achievement of mathematics students were inclined by ICP. However, giving English instruction in the classroom should be continued frequently in every semester because it helps the students to remember and maintain their English as students of ICP.